Mycotoxigenic fungal growth inhibition and multi‑mycotoxin reduction of potential biological control agents indigenous to grain maize - Yazid, Siti Nur Ezzati; Tajudin, Nur Izzah; Razman, Nur Aina Aribah; Selamat, Jinap; Ismail, Siti Izera; Sanny, Maimunah; Samsudin, Nik Iskandar Putra (Springer, 2023)
The present work investigated the potential of fungal species from grain maize farms in Malaysia as antagonists against the indigenous mycotoxigenic fungal species and their subsequent mycotoxin production. Dual-culture assay was conducted on grain maize agar (GMA) with 12 strains of potential fungal antagonists namely Bjerkandra adusta, Penicillium janthinellum, Schizophyllum commune, Trametes cubensis, Trichoderma asperelloides, Trichoderma asperellum, Trichoderma harzianum, and Trichoderma yunnanense against seven mycotoxigenic strains namely Aspergillus flavus, Aspergillus niger, Fusarium verticillioides, and Fusarium proliferatum producing aflatoxins, ochratoxin A, and fumonisins, respectively. Based on fungal growth inhibition, Trichoderma spp. showed the highest inhibitory activity (73–100% PIRG, Percentage Inhibition of Radial Growth; 28/0 ID, Index of Dominance) against the tested mycotoxigenic strains. Besides, B. adusta and Tra. cubensis showed inhibitory activity against some of the tested mycotoxigenic strains. All fungal antagonists showed varying degrees of mycotoxin reduction. Aflatoxin B1 produced by A. flavus was mainly reduced by P. janthinellum, Tra. cubensis, and B. adusta to 0 ng/g. Ochratoxin A produced by A. niger was mainly reduced by Tri. harzianum and Tri. asperellum to 0 ng/g. Fumonisin B1 and FB2 produced by F. verticillioides was mainly reduced by Tri. harzianum, Tri. asperelloides, and Tri. asperellum to 59.4 and 0 µg/g, respectively. Fumonisin B1 and FB2 produced by F. proliferatum were mainly reduced by Tri. asperelloides and Tri. harzianum to 244.2 and 0 µg/g, respectively. This is the first study that reports on the efficacy of Tri. asperelloides against FB1, FB2, and OTA, P. janthinellum against AFB1, and Tra. cubensis against AFB1.